The influence of brand awareness, brand ambassador, and brand image on the purchasing decision of viva beauty products in Batam City - Hera Melawati; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2025)
This study investigates the influence of Brand Awareness, Brand Ambassador, and Brand Image on Purchase Decisions for Viva Cosmetics products. Employing a quantitative approach, data were collected through questionnaires distributed to 119 respondents, primarily female consumers aged 21–30 years. The data were analyzed using SPSS 25 through validity, reliability, classical assumption, and multiple linear regression tests. The results show that all three independent variables have a positive and significant effect on purchase decisions, with Brand Awareness emerging as the most influential factor, followed by Brand Image and Brand Ambassador. The regression model indicates that increased awareness, ambassador credibility, and brand image contribute to stronger consumer purchasing intentions. The coefficient of determination (R² = 0.740) suggests that 74% of purchase decision variations are explained by the three variables, while 26% are influenced by other factors not examined in this study. The findings highlight the importance of integrated branding strategies, emphasizing consistency, ambassador authenticity, and brand identity reinforcement to strengthen consumer loyalty and purchasing behavior in the competitive Indonesian cosmetics market..